Developing Life Skills in the Family: Strategies Strengthening Childrens’ Social and Emotional Intelligence - Τσώλη Κωνσταντίνα (Education Sciences, 2022)
The aim of this study is to discuss the importance of cultivating life skills in the family framework and to emphasize the need for social and emotional education of children. In particular, theoretical models, examples, and case studies of psychopedagogical content describe the types of parents based on their responses to their children's emotions, and a model of social and emotional education that aims at their overall healthy development is suggested. The proposed strategies and suggestions for emotional education suggest a parent who will act supportively and empathetically to the needs of his child, that is, as an emotional "mentor" - "coach".